ANALYTICAL INDICATORS OF HUMAN RESOURCE MANAGEMENT METHODS: A CASE STUDY OF UZBEKISTAN - Khaydarova Malika Shokirjon kizi (Ecomind Press, 2025)
This research focuses on studying the analytical indicators of human resource management methods in Uzbekistan. The study analyzes HR indicators used in public and private enterprises in Uzbekistan, their effectiveness, and modern trends. Based on statistical data, the study examines the impact of HR indicators on economic development, employee satisfaction, and labor productivity. The research results indicate that it is necessary to develop the human resource management system in Uzbekistan, implement indicators adapted to international standards, and improve the HR monitoring system based on digital technologies. This, in turn, serves to increase the competitiveness of enterprises and ensure economic stability.
Keywords: Human resources, analytical indicators, HR management, HR effectiveness, labor productivity, Uzbekistan.